Internet of Things (IoT): Is IoT a Disruptive Technology or a Disruptive Business Model? - Narasimha Murthy, D.; Vijaya Kumar, B. (Indian Journal of Marketing, 2015)
The purpose of this paper was to describe how the newly emerging "Internet of Things" (IoT) will provide unprecedented opportunities to penetrate technology and automation into everything we do, and at the same time, provide a huge playing field for businesses to develop newer business models to capture market share. The information available on the Internet today is mostly constrained by the number of users generating the content. Internet users have grown from several thousand a few years ago to 2.8 billion in 2014 and is estimated to grow to 6.5 billion in 2020. Imagine a situation where we augment the effort of today's data collection method by using "Things with sense - called Sensors" to automatically collect, store, and analyze data. With the advancements in hardware, wireless networking, and cloud computing, this data can be stored, analyzed, and used. The number of sensors is projected to grow from 7 billion in 2014 to over 50 billion in 2020, with each person on earth carrying an average of seven devices. This explosion in the "things" used and subsequently, the data being collected will not only impact major service providers like semiconductor, networking, and device manufacturers, but will also redefine the current product offering and branding strategies. There will be a huge opportunity for businesses to provide a variety of customized products and services, the prominent ones being automobiles, healthcare, home control systems, environment protection, and manufacturing.